2012
DOI: 10.1111/j.1529-8027.2012.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of repeater F‐waves in the early stage of Guillain‐Barré syndrome

Abstract: The absence or a prolonged latency of late responses, like F‐waves, is a common neurophysiological finding with diagnostic utility in the early Guillain‐Barré syndrome. However, the presence and the number of repeater F‐waves have not been studied in this disease. In four patients, we report the transient presence of repeater F‐waves in nerves of the lower limbs shortly after the onset of the disease. In each patient, the initial (diagnostic) nerve conduction study showed a high incidence of repeater F‐waves i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…A possible explanation for this discrepancy could be that in AMAN cases characterized by reversible conduction failure, A‐waves disappear in follow‐up studies while F‐wave persistence recovers (Figure 3). Regarding Freps frequency in early stages of GBS, our results are in agreement with Geijo‐Barrientos et al, who previously reported an increased presence of Freps in lower limb nerves 11 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A possible explanation for this discrepancy could be that in AMAN cases characterized by reversible conduction failure, A‐waves disappear in follow‐up studies while F‐wave persistence recovers (Figure 3). Regarding Freps frequency in early stages of GBS, our results are in agreement with Geijo‐Barrientos et al, who previously reported an increased presence of Freps in lower limb nerves 11 …”
Section: Discussionsupporting
confidence: 93%
“…The presence of repeater F‐waves (Freps) and A‐waves are not routinely studied in GBS patients. An increased frequency of Freps has been reported in various neuropathies including GBS 6‐11 . A‐waves are observed in both acute and chronic neurogenic conditions that vary widely in underlying pathophysiological mechanisms 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic finding of F‐waves in polio survivors was abundant repeater F‐waves with a high occupancy rate. The occurrence of repeater F‐waves has been demonstrated in carpal tunnel syndrome, motor neuron disease, cervical spondylosis, lumbosacral radiculopathy, and Guillain‐Barré syndrome . The ORFs of the polio group were approximately 4‐46 times greater than those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The response may be motor or sensory, depending on the nerve involved) [ 6 ]; prolonged or repeater F-waves (a F-wave is obtained via supramaximal stimulation of the motor nerve in the distal site. This causes the stimulus to reach the proximal (toward the neurons of the spinal cord) motor neurons and they fire, leading to a stimulus, which is measured as the F-wave) [ 7 ] along with conduction blocks [ 8 ]; and increased A-waves (an A-wave is recorded during routine F-wave studies. It appears during the acute stage of AIDP.…”
Section: Guillain–barre Syndromementioning
confidence: 99%